2015
DOI: 10.1155/2015/684618
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation of the Relationship between PM2.5Concentrations and Meteorological Parameters in China

Abstract: Epidemiological studies around the world have reported that fine particulate matter (PM2.5) is closely associated with human health. The distribution of PM2.5 concentrations is influenced by multiple geographic and socioeconomic factors. Using a remote-sensing-derived PM2.5 dataset, this paper explores the relationship between PM2.5 concentrations and meteorological parameters and their spatial variance in China for the period 2001–2010. The spatial variations of the relationships between the annual average PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…In addition, the results indicated that PM 2.5 -induced effects varied by season. The observed seasonal differences on PM 2.5 concentrations and effect estimates might be explained by variations in meteorological parameters, the chemical composition of PM 2.5 and exposure patterns [ 23 , 33 , 34 ]. Sea-land breezes (SLBs) that prevail in summer bring abundant moisture, which could reduce the concentrations of atmospheric particles in southwestern Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results indicated that PM 2.5 -induced effects varied by season. The observed seasonal differences on PM 2.5 concentrations and effect estimates might be explained by variations in meteorological parameters, the chemical composition of PM 2.5 and exposure patterns [ 23 , 33 , 34 ]. Sea-land breezes (SLBs) that prevail in summer bring abundant moisture, which could reduce the concentrations of atmospheric particles in southwestern Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between air pollution and meteorological parameters have been reported in cities worldwide, such as New York [17], Paris [18], Amsterdam [19], Beijing [10,20], Delhi [21], Nagasaki [22], and Seoul [23]. In China, the North China Plain (NCP), Yangtze River Delta (YRD), and Pearl River Delta (PRD) are air pollution research hotspots due to their dense pollution, developed economies, and deteriorated air quality, whereas vast northwestern regions have attracted less attention [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Shenyang, Harbin, Lanzhou, Jinan, Tianjin, and Changsha were regions that were industrialized relatively early and have suffered from air pollution prior to the 1950s [52]. Throughout the process of rapid urbanization and industrialization, the governments of these cities established environmental management policies earlier than other cities, thus the AV of these cities did not deteriorate significantly during the period of our study [46]. Shenyang and Harbin, as developed industrial cities, are the important industrial cities in northern China and have been centers for heavy industry in China since the 1930s.…”
Section: Special Characteristics Of Atmospheric Visibility Trends In mentioning
confidence: 89%
“…Seasonal variations reflect most of the effects of meteorological conditions, such as those impacted by emissions from the global desert and residents' activities. During winter and spring, AV is relatively low due to two factors: stagnant meteorological conditions characterized by slow winds and shallow mixing layers occur more frequently, and there is a higher concentration of air pollutants due to the trapping of pollutants near the atmospheric surface [45][46][47]. Furthermore, emissions from the global desert are also a reason for low AV during spring and winter in northern and western China [48].…”
Section: Seasonal Variation Of Atmospheric Visibility In 31 Pccs Of Cmentioning
confidence: 99%